Natural convection heat transfer in a partially opened cavity filled with porous media - Öztop, Hakan Fehmi; Al-Salem, Khaled; Varol, Yasin; Pop, Ioan (Pergamon-Elsevier Science Ltd, 2011)
This paper examines the steady natural convection in a partially opened enclosure filled with porous media using the Brinkman-Forchheimer model. Whilst the part of the left vertical wall of the cavity is heated, the other walls are adiabatic or thermally insulated Based upon numerical predictions, the effects of pertinent parameters such as Grashof number, Darcy number, porosity, length of the heated wall and the location center of the opened cavity are examined. It is found that as the Grashof number increases, due to strengthening buoyancy driven flows, the local Nusselt number from partially heated vertical wall, at a given position on this wall increases. This. in turn, increases the temperature of the heated wall. The results of this study can be used in the design of an effective cooling system for electronic components to help ensure effective and safe operational conditions. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Natural convection; Open cavity; Partial heating; Porous media